Pelatihan Kemampuan Manajemen Keuangan Sederhana Bagi Guru SMP IT Daarul Istiqlal Marindal-I - Hasibuan, Melisa Zuriani; Jayusman, Sri Fitria; Munawaroh, Munawaroh; Siregar, Horia; Wulandari, Sari (Yayasan Rahmat Islamiyah, 2024)
The general objective of financial management is to achieve certain funding targets in the future. Then protect and increase your wealth. Next, manage cash flow (incoming and outgoing money) and carry out risk management and manage investment risks well and manage debts and receivables. Something that is always related to financial management is bookkeeping, which is an activity consisting of recording, reporting and analyzing business conditions (evaluation) which is carried out in an orderly, regular, chronological and systematic manner. Based on the PKM-PM team survey, the problems that exist at Daarul Istiqlal IT Middle School are, Based on the PKM team survey, the problem that exists at Daarul Istiqlal Marindal I IT Middle School is that teachers still have low knowledge and understanding in managing finances in a simple way. The solution offered is the aspect of improving performance management. The solution that will be offered is to provide intensive assistance to partners by focusing on improving partners' skills in carrying out the learning process and can become a model school for other schools. From the results of the questionnaire, it was found that Daarul Istiqlal IT Middle School service participants' interest in practicing this service activity had been successful. Around 80% of the entire community participated and felt happy to take part in this training because it could increase their insight into simple financial management. Partners really contribute to the smooth running of community service activities.